El embarazo no exacerba la dermatomiositis. - BERROCAL, Alfredo; RAMÍREZ, Erick; CALVO, Armando (Revista Médica Herediana, 2013)
We report four pregnancies in three dermatomyositis female patients who had their disease under control from beginning, during the course of their pregnancies, and the Postpartum period. Two females were off steroids and one received prednisone and azathioprine until week 16th of pregnancy when azathioprine was taken off, remaining only on prednisone, Neither case had a disease relapse. All babies were alive and full term newbornes, they also were adequate for gestational age and none had congenital malformations.